Methodological aspects of measuring levels of veterans’ social adaptation - Bataeva, Ekaterina; Artemenko, Anna (Technium Social Sciences Journal, 2020)
This paper presents the classical and modern sociological approaches to the analysis of social adaptation and integration; the features of social adaptation of veterans of armed conflicts are revealed. The methodology for measuring the levels of social adaptation of veterans of armed conflicts is presented and tested. It has been found that the majority of Ukrainian veterans has the middle level of social adaptation (39%); they currently need support from society in order to finally adapt to civilian life. 33% of veterans have not adapted to civilian life; such veterans usually do not have a job/housing/family/children. 28% of Ukrainian veterans have high level of social adaptability.